Cyclodextrin Derivatives as Promising Solubilizers to Enhance the Biological Activity of Rosmarinic Acid - Anna Stasiłowicz-Krzemień; Natalia Rosiak; Anita Płazińska; Wojciech Płaziński; Andrzej Miklaszewski; Ewa Tykarska; Judyta Cielecka-Piontek (MDPI AG, 2022)
Rosmarinic acid (RA) is a natural antioxidant with neuroprotective properties; however, its preventive and therapeutic use is limited due to its slight solubility and poor permeability. This study aimed to improve RA physicochemical properties by systems formation with cyclodextrins (CDs): hydroxypropyl-α-CD (HP-α-CD), HP-β-CD, and HP-γ-CD, which were prepared by the solvent evaporation (s.e.) method. The interactions between components were determined by X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC) and Fourier Transform infrared spectroscopy (FTIR). The sites of interaction between RA and CDs were suggested as a result of in silico studies focused on assessing the interaction between molecules. The impact of amorphous systems formation on water solubility, dissolution rate, gastrointestinal (GIT) permeability, and biological activity was studied. RA solubility was increased from 5.869 mg/mL to 113.027 mg/mL, 179.840 mg/mL, and 194.354 mg/mL by systems formation with HP-α-CD, HP-β-CD, and HP-γ-CD, respectively. During apparent solubility studies, the systems provided an acceleration of RA dissolution. Poor RA GIT permeability at pH 4.5 and 5.8, determined by parallel artificial membrane permeability assay (PAMPA system), was increased; RA-HP-γ-CD s.e. indicated the greatest improvement (at pH 4.5 from Papp 6.901 × 10−7 cm/s to 1.085 × 10−6 cm/s and at pH 5.8 from 5.019 × 10−7 cm/s to 9.680 × 10−7 cm/s). Antioxidant activity, which was determined by DPPH, ABTS, CUPRAC, and FRAP methods, was ameliorated by systems; the greatest results were obtained for RA-HP-γ-CD s.e. The inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) was increased from 36.876% for AChE and 13.68% for BChE to a maximum inhibition of the enzyme (plateau), and enabled reaching IC50 values for both enzymes by all systems. CDs are efficient excipients for improving RA physicochemical and biological properties. HP-γ-CD was the greatest one with potential for future food or dietary supplement applications.